ANALISIS KELAYAKAN INVESTASI PEMBANGUNAN READY MIX PLANT (STUDI KASUS PT. X DI JAWA TIMUR) - Wilda Itatul Izza, Susapto, Fadjar Purnomo (Prokons: Jurnal Teknik Sipil, 2019)
PT. X will built a 3,000-m2 ready mix plant able to demand of X-Y highway contruction project. The built was planned in 3 alternative site: in Gempol—72.6km from the project site, in Purwosari—44.6km from project site, and in Singosari—53km from project site . The purpose of this study is: 1) to determine investment feasibility by technical aspect of each alternative site; 2) to determine investment feasibility by financial aspect based on feasibility parameters; 3) to determine the level of sensitivity of financial feasibilty by seeing the increase of materials and operational costs, the decrease of selling price and product demand.Technical feasibility was analyzed based on the result of questionnaires by calculating the percentage of each variable such as materials; man power; equipment; transportation; provision of water, electricity, and telephone line; and circumstances of social, environtment, community. The percantage of variable was of influential factor to choose the site by ranking method. Financial feasibility resulted from the cost of each site was analyzed based on feasibility parameter of Net Present Value (NPV), Benefit Cost Ratio (BCR), Internal Rate of Return (IRR), and Payback Period (PP). The last analysis was the sensitivity one to determine the level of sensitivity by seeing the increase of materials and operational costs, the decrease of selling price and product demand.The result of investment feasibility by technical aspect is feasible in Purwosari, Pasuruan District with a close range of raw materials; adequate availability of man power; adequate equipment; adequate transportation facilities; provision of water, electricity, and telephone lines; supporting from social, environtment, and community. The investment feasibility is financially feasible at NPV = IDR7,075,213,700; BCR = 1.047; IRR = 64.875%, and PP = 1,13 year. The result of sensitivity analysis shows that the PT. X is still able to adjust the 1%-8% tollerable increasing materials cost, 1%-7% increasing operational cost, 1%-6% decreasing selling price, and 1%-6% decreasing product demand. Keywords: BCR, feasibility, investment, IRR, NPV, PP, ready mix plant, sensitivity.